Conservation action implementation, funding, and population trends of birds listed on the Endangered Species Act. (May 2016) - Luther, David; Skelton, James; Fernandez, Christopher; Walters, Jeffrey
Abstract: Current rates of species endangerment and extinction are unprecedented in modern times. Conservation efforts aim to slow down, stop, and reverse threats to species and thus the current loss of biodiversity. However, the extinction risk to species continues to rise. Thus far, research has examined the efficiency and the effectiveness of conservation actions individually, yet, the full suite of implemented conservation actions should be considered. We assessed all implemented conservation actions for avian species listed under the Endangered Species Act (ESA) in the United States. Using data available through the US Fish and Wildlife Service (USFWS) we assessed the relationships between conservation actions implemented, population trends, and financial expenditures for all listed species each year between 1996 and 2013. We found positive associations between the amount of funding allocated for a species and their population trend. Implementation of the conservation actions habitat protection and educational awareness were positively associated with annual funding for a species. Our results highlight the disparity in conservation action implementation and resource allocation between ESA listed species on the mainland and on islands in the USA. Together these results and the cause and effect relationships they suggest could provide a pathway toward more effective conservation programs. Highlights: Ten fold difference between expenditures for continental and island species Association between expenditures and increasing population trends Associations between expenditures and habitat protection Major differences between conservation action implementation and population trends for species on continents and islands